Ответы и объяснения

2013-10-14T13:15:53+00:00
1)a)  \frac{ (2x-1)^{2} }{4} =(x-2)(x+2)
 \frac{4  x^{2}  - 4x +1}{4} -  x^{2} +4=0
привели к общему знаменателю и получилось :  \frac{-4x+17}{4} = 0
-4x+17=0
4x=17
x= \frac{17}{4}
б)5x^2 - (5x-1)(x+2)=0
5x^2 - 5x^2 - 9x + 2 = 0
-9x+2=0
x=  \frac{2}{9}
2) a) это формула сокращенного умножения   (3x-5)^{2}
б) x^2 - y^2 - 2y - 1= (x^2-1) (-y-2y)= (x-1)(x+1)-y(y+2)
3) a)  \frac{3a^2 - 27}{18-6a} =  \frac{3(a^2 - 9)}{6(3-a)} =  \frac{(a-3)(a+3)}{2(3-a)} = -  \frac{a+3}{2}
б) \frac{(a-b)(a+b)- (a-b)^{2} }{b(a-b)} =  \frac{(a-b)2b}{b(a-b)} = 2
4) a)привели к общему знаменателю:  \frac{a^2+ab-ab+b^2}{(a-b)a+b)} =  \frac{a^2 + b^2}{a^2 - b^2}
б) (x+x^2) : (1+ \frac{1}{x} )=(x+x^2) : ( \frac{x+1}{x} ) = x(1+x) *  \frac{x}{x+1} = x^2